A comparative study on the efficacy of over-the-counter wax solvents versus distilled water for managing ear cerumen - Syed. Mohd. Ahmad; Rajesh Kumar Suman; Simran Kaur Pal; Ayush Agrawal (MGM Journal of Medical Sciences)
Background: Ear wax, or cerumen, is a naturally occurring hydrophobic waxy substance frequently encountered in otorhinolaryngology practices. Despite the abundance of water- and oil-based ceruminolytic agents available nowadays, there remains a lack of consensus regarding the preferred agent type, composition, or ideal treatment duration. Aims and Objectives: The study aimed to assess the efficacy of using distilled water as a wax-softening agent for ear wax removal and determine its advantages compared to over-the-counter (OTC) ceruminolytics. Materials and Methods: This double-masked, randomized prospective cohort study enrolled 236 patients seeking treatment for ear wax-related concerns at the Ear, Nose, Throat outpatient department. The cohort exclusively consisted of cases involving right ear wax, which were then randomly allocated into two groups: group A received distilled water ear drops, whereas group B received OTC ceruminolytic ear drops containing a combination of paradichlorobenzene with turpentine oil, benzocaine, and chlorbutol. Evaluation of patients took place pre- and post-intervention, focusing on three key parameters: the total duration required for ear suctioning, any additional instrumentation employed, and the occurrence of pre-procedure and post-procedure complications. Results: Out of the total 118 participants in the study, they were randomly distributed with 67 males and 51 females in group A and 63 males and 55 females in group B. During the pre-intervention complication assessment, nine subjects in group A reported ear blockage, whereas four subjects in group B did so. Additionally, two subjects in group A complained of pain, whereas none in group B did. Furthermore, five subjects in group A developed otitis externa, compared with three in group B. The average time required for ear suctioning to visualize the tympanic membrane was 9.24 ± 2.50 min in group A and 9.68 ± 2.18 min in group B. During the intervention, nine subjects in group A experienced pain during wax removal, whereas only six patients in Group B reported pain. After the interventions, five patients in group A complained of increased ear pain compared with seven in group B. Mild post-interventional pain was managed with an as-needed dosage of nonsteroidal anti-inflammatory drugs Statistically significant differences were observed in the study parameters between the subjects of the two groups. Conclusion: This study confirms that distilled water can serve as a viable method for dispersing wax, proving its efficacy comparable with commercially available OTC ceruminolytics.